Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Multiply (2r+5) by (r+3) through foil method...
First Term: 2r and r=2 r^{2}
Outer Term: 2r and 3=6r
Inner Term: 5 and r= 5r
Last Term: 3 and 5= 15
So (2r+5)(r+3)=2 r^{2} +6r+5r+15 (You can add 5r and 6r and it will result in 2 r^{2} +11r=15.
1 5 1
salamat po though tapos na. komawo :D
You're Welcome... :-)
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts